2002
DOI: 10.1046/j.0007-1323.2001.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial assessing the side-effects of glyceryl trinitrate and diltiazem hydrochloride in the treatment of chronic anal fissure

Abstract: DTZ cream caused substantially fewer headaches than GTN ointment. There was no significant difference in the healing or improvement of chronic anal fissure between the treatments. DTZ may be the preferred first-line treatment for chronic anal fissure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 16 publications
1
75
0
3
Order By: Relevance
“…Oral diltiazem caused side effects such as rash, headache, nausea, vomiting, decreased smell and taste, whereas topically treated groups showed no side effects. Kocher et al [17] showed adverse effects of GTN and diltiazem in the treatment of chronic anal fissure. Diltiazem therapy was shown to cause less headache than GTN therapy [P=0.01].…”
Section: Resultsmentioning
confidence: 99%
“…Oral diltiazem caused side effects such as rash, headache, nausea, vomiting, decreased smell and taste, whereas topically treated groups showed no side effects. Kocher et al [17] showed adverse effects of GTN and diltiazem in the treatment of chronic anal fissure. Diltiazem therapy was shown to cause less headache than GTN therapy [P=0.01].…”
Section: Resultsmentioning
confidence: 99%
“…37 The topical formulation of diltiazem has been subjected to rigorous scrutiny and is a valid alternative to GTN with similar reductions in MRP, improved healing rates and lower rates of recurrence. [38][39][40][41] There are also data to suggest that topical diltiazem heals GTN-resistant fissures. 42 …”
Section: Calcium Antagonistsmentioning
confidence: 99%
“…The incidence of anal fissure was slightly higher in males than in females which is comparable to Kocher et al study where incidence of anal fissure is slightly higher in males. 5 After six weeks, complete pain relief was seen in 38 patients out of 50 patients in Lignocaine group and 46 patients out of 50 patients in Combination group. Results of the present were similar to study conducted Lund et al where 18 out of 21 patients were asymptomatic after second week of treatment and Mann et al where 15 out of 16 patients were asymptomatic after four weeks.…”
Section: Discussionmentioning
confidence: 96%